Validity of the Deed of the Official Writing the Land Deed in the Event of Legal Problems in Credit Agreements With Credit Rights as Security - Nur Hamidah, Britania; Fajar Riyanto, Taufan (Jurnal Konstatering, 2025)
An authentic deed contains the concept of truth regarding the deed in proving that the parties have understood and explained what is written in the deed, including explaining that the deed is true. Authentic deeds can also be said to have perfect evidentiary power because they have three types of evidentiary power, namely physical, formal and material. The role of a notary is not only administrative, but also preventive, namely preventing potential disputes in the future through the creation of deeds that are clear, complete and in accordance with the provisions of the law. In addition, there are factors causing default related to the role of the notary, where default in a credit agreement with collateral can be caused by various factors, both internal to the notary and external factors. This study uses a normative juridical approach with a case study approach and analysis of applicable laws and regulations, particularly the Land Deed Official Law and its implementation. The data obtained uses literature studies obtained from secondary data on legal literature, court decisions, and documents related to the preparation of this scientific work, and the analysis in this study is perspective. The results of the study show that the validity of PPAT deeds depends on the simultaneous fulfillment of formal and material requirements. Failure to fulfill either of these requirements will result in the deed being invalid.Keywords: Land Deed Official, Credit Agreement, Mortgage Rights